1989
DOI: 10.1073/pnas.86.15.5864
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydrobiopterin, the cofactor for aromatic amino acid hydroxylases, is synthesized by and regulates proliferation of erythroid cells.

Abstract: The only known role for 6(R)-5,6,7,8-tetrahydrobiopterin (BH4) is as the cofactor for the aromatic amino acid hydroxylases. However, BH4 has been shown to be synthesized by cells that do not contain any hydroxylase activity, suggesting that it may have still undiscovered functions. Our fmding of much higher levels of BH4 and GTP by the sequential reductions of sepiapterin reductase and dihydrofolate reductase. Treatment of MEL cells with hexamethylene bisacetamide, an inducer of differentiation, results in a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(39 citation statements)
references
References 28 publications
1
38
0
Order By: Relevance
“…We previously found that erythropoietic cells, despite the lack of any known BH 4 -dependent hydroxylation reactions, synthesized and contained high levels of BH 4 , which appears to play a regulatory role as a switch between growth and differentiation (52). Furthermore, we showed that proliferation of primary astrocytes was also regulated by endogenous BH 4 levels (53), results that were later confirmed in several other types of cells (54,55).…”
Section: Discussionsupporting
confidence: 62%
“…We previously found that erythropoietic cells, despite the lack of any known BH 4 -dependent hydroxylation reactions, synthesized and contained high levels of BH 4 , which appears to play a regulatory role as a switch between growth and differentiation (52). Furthermore, we showed that proliferation of primary astrocytes was also regulated by endogenous BH 4 levels (53), results that were later confirmed in several other types of cells (54,55).…”
Section: Discussionsupporting
confidence: 62%
“…The only pathway of apoptotic cell death that is blocked by either zVAD-fmk, olomoucine, or NAC is that of trophic factor deprivation (36,60). Previous reports suggested that BH 4 can induce cell proliferation (16,71) and that growth factor-induced proliferation correlates with endogenous BH 4 levels in PC12 cells (17). In view of these data, we postulate that BH 4 affects a growth factor-dependent signaling event, which leads to increased proliferation in the presence of sufficient trophic support or enhances cell death in its absence.…”
Section: Effect Of N-acetylcysteine or Inhibition Of Cyclin-dependentmentioning
confidence: 99%
“…Why extracellular, but not intracellular, BH4 is toxic is not clear at present. Interestingly, elevation of intracellular BH4 has been reported to enhance proliferation (Tanaka et al, 1989;Anastasiadis et al, 1996) and to protect cells against oxidative stressors (Ishii et al, 1999;Nakamura et al, 2000) in various cell types. We have also observed in the present study that elevation of intracellular BH4 with sepiapterin was not toxic.…”
Section: Downloaded Frommentioning
confidence: 99%